Evaluation of the elastic behavior of multiaxis 3D-woven preforms by numerical approach. (November 2014) - Labanieh, Ahmad Rashed; Legrand, Xavier; Koncar, Vladan; Soulat, Damien
Compared to the laminated composite made of two-dimensional preform, the three-dimensional-woven composites have been evolved as an attractive structural material. Based on the classical textile technologies such as weaving, braiding, and knitting, complex preforms have been fabricated as reinforcement for technical applications. In the recent years, many studies have been published on the development of modeling techniques to design, analyze, and understand the effect of the preform architecture on its mechanical behavior. In this paper, we propose to use these numerical approaches to evaluate the mechanical performance of multiaxis three-dimensional-woven preform. Also, comparisons of the estimated mechanical properties of this structure with that of 3D orthogonal-woven preform and that of classical laminate are conduced.